Characterization Bio-Based Edible Film from Mango Seed Starch and Semi-Refined Carrageenan (Euchema cottonii) Using Sorbitol Plasticizer for Potential Food Contact Materials - Sintha Soraya Santi; Ika Nawang Puspitawati; Tim Pasang (Postgraduate, University of Mataram, 2024)
Meanwhile, Semi-Refined Carrageenan (SRC) could be combined with starch as the base material for edible film fabrication to increase its tensile strength. This study aimed to identify edible film by synthesizing SRC and mango seed starch with plasticizer sorbitol, which could be safe for consumption in food packaging. The process of making edible film consists of three steps: extracting Eucheuma cottonii seaweed, making starch from mango seeds, and making edible film. The method used was the solution casting method, with a ratio of SRC: starch of mango seeds, namely 1: 0; 0.7: 0.3; and 0: 1 (w / w) and sorbitol concentrations of 20, 30, 40, 50, and 60% (w/w). This research shows that increasing sorbitol could decrease the tensile strength but increase the elongation and solubility of the edible film. As well as the combination of SRC and mango seed starch can produce edible films with higher characteristics than edible films based only on SRC or mango seed starch. The results of selecting the best conditions for an edible film based on the Japanese Industrial Standard (JIS) are the concentration ratio of SRC: mango seed starch (0.7: 0.3) and 30% sorbitol concentration with a thickness value of 0.22 mm, tensile strength 4.81 MPa, 28.50% elongation and 68.44% solubility